From Concrete Objects to English Words: Rethinking Vocabulary Learning for Young Learners with Intellectual Disability - Ririn Ambarini (Indo Publishing, 2026)
English vocabulary learning can be challenging for young learners with intellectual disability, particularly when new words are presented without meaningful connections to familiar experiences. This qualitative case study explored how concrete objects were used to support English vocabulary learning among Grade II students with intellectual disability at SLB Negeri Semarang. Data were collected through classroom observations, semi-structured interviews, and documentation and were analyzed thematically. The findings indicate that concrete objects provided a meaningful starting point for vocabulary learning by enabling students to recognize familiar objects before connecting them with corresponding English words. Students demonstrated their learning through various verbal and non-verbal responses, including looking, pointing, touching, selecting objects, imitating pronunciation, and attempting to produce target words. Teacher scaffolding through modeling, repetition, gestures, prompting, and feedback further supported the connection between concrete objects and English vocabulary. The findings suggest that vocabulary learning for young learners with intellectual disability should be understood as a gradual and multimodal process rather than solely through immediate verbal production. Concrete objects can function as learning anchors that help learners move from concrete experience toward English word recognition and emerging production.